Various Natural Ingredients as Plant Growth Regulator to Increasing Viability True Seed Shallot of Onion - Elseria Siburian; Luthfi A.M. Siregar (Talenta Publisher, 2019)
The research was aimed to determine the source of plant growth regulator from natural ingredients that can increase the viability of onion True Seed Shallot (TSS). This research was conducted at the Laboratory of Seed, Universitas Sisingamangaraja XII Tapanuli, North Sumatra from June until July 2018. This research used Completely Randomized Design. The treatment of this research: Z0 (control/distilled water), Z1 (GA3 100 ppm), Z2 (BAP 100 ppm), Z3 (banana hump extract), Z4 (bamboo shoot extract), Z5 (onion extract), Z6 (coconut water). Each treatment has four replications. Parameters of this research include maximum growth potential (MGP), germination, root length, and hypocotyl length. Data analysis using IBM SPSS Statistics v.20. The results showed that treatment onion extract can increase the highest TSS germination at 7 and 14 days after planting (DAP) amount 85.83% and 80.84% respectively. Treatment bamboo shoots, onion extracts, coconut water and GA3 can increase the MGP which is classified as high ranging from 81.67 to 92.50%. Soaking the onion TSS with bamboo shoot extract and GA3 treatment can increase the hypocotyl length amount 4.06 cm and 3.91 cm respectively.